Brexit e soberania: estudo sobre a reterritorialização em uma perspectiva geopolítica - Nascimento, Vinícius Ricardo do (2022)
This dissertation aimed to analyze the multidimensional (HAESBAERT, 2003) and polymorphic (BRENNER, 2018) process of the United Kingdom's exit from the European Union through Brexit, initiated in 2016 and consolidated in 2020 after years of negotiations. The focus was on the legal-political dimension of the territory (material and symbolic) through the reterritorialization of British sovereignty to the detriment of the supranational deterritorialization of the European regional bloc. Furthermore, the culturalist and economic dimensions of Brexit were also addressed as related axes. A geopolitical scenario of contradictions and conflicts, dualities and dichotomies: the Leave campaign and the Remain campaign, British autonomy and insular identity versus the heteronomy of institutions, nationalism against supranationality, local versus global.